Effects and Remedies of Construction Claims in Hydropower Projects: Case Studies of Selected Medium-Scale Hydropower Projects in Nepal - Tamang, Suraj; Kayastha, Gyanendra Prasad; Adhikari, Prabesh (New Perspective: Journal of Business and Economics, 2024)
This research aims to analyze the perspectives of various stakeholders involved in hydropower projects, including employers, engineers, and contractors, to identify common challenges and propose strategies for minimizing claims. The data analysis involved a questionnaire survey conducted among representatives of employers, engineers, and contractors across seven selected hydropower projects. Similar questionnaires were distributed to gather insights from all three parties involved in the projects. The responses were compiled and analyzed collectively using a general ranking method, allowing for a comprehensive assessment of the findings related to the thesis objectives. The analysis revealed that claims significantly impact construction projects, manifesting as both cost overruns and time delays. If not addressed promptly, these claims can escalate into disputes that typically require resolution through Alternate Dispute Resolution (ADR) procedures or may lead to complex legal proceedings. The study identified several key factors contributing to claims, including inadequate tender documentation, poor record-keeping of daily site events, and the occurrence of major design changes. To mitigate the risks associated with claims in hydropower projects, it is essential to implement several best practices: preparing clear and unambiguous tender documents, maintaining comprehensive daily records of site activities, minimizing design changes whenever possible, ensuring site possession prior to contractor mobilization, and conducting thorough field investigations before finalizing designs.